Initial electron-transfer in the reaction center from Rhodobacter sphaeroides. - Holzapfel, W (1990)
The initial electron transfer steps in the photosynthetic reaction center of the purple bacterium Rhodobacter sphaeroides have been investigated by femtosecond time-resolved spectroscopy. The experimental data taken at various wavelengths demonstrate the existence of at least four intermediate states within the first nanosecond. The difference spectra of the intermediates and transient photodichroism data are fully consistent with a sequential four-step model of the primary electron transfer: Light absorption by the special pair P leads to the state P*. From the excited primary donor P*, the electron is transferred within 3.5 +/- 0.4 ps to the accessory bacteriochlorophyll B. State P+B- decays with a time constant of 0.9 +/- 0.3 ps passing the electron to the bacteriopheophytin H. Finally, the electron is transferred from H- to the quinone QA within 220 +/- 40 ps.